Geschichte fürt zu einem Bewusstsein – Gerechtigkeit und Machtkritik als leitende Prinzipien im Lukaskommentar von Hans Klein - SOMMER, Michael (Studia Universitatis Babeș-Bolyai Sacra Scripta, 2026)
This article offers a critical appreciation of Hans Klein’s commentary on the Gospel of Luke, focusing on justice and power critique as its guiding hermeneutical principles. It argues that, although Klein rarely develops justice as an explicit concept, it functions as a structural core of his interpretation. Klein’s historically and socially sensitive reading presents Luke as a narrator deeply attuned to poverty, marginalization, and asymmetrical power relations. By examining selected Lukan pericopes, the study shows how Klein integrates exegesis with ethical responsibility, portraying justice as a lived, politically relevant dimension of discipleship rather than a merely abstract theological category.